Дослідження термостійкості та форм зв’язку вологи в насінні рицини методами термічного та термогравіметричного аналізів - Колесніченко, Ірина Анатоліївна; В’юник, Ольга Володимирівна; Kolesnichenko, Iryna; Viunyk, Оlha (Запоріжжя : Видавничий дім «Гельветика», 2026)
UA: У роботі розглянуто особливості термостійкості насіння рицини та форми зв’язку вологи в його структурі з використанням методів термічного і термогравіметричного аналізів. Показано, що під час теплової обробки насіння рицини відбуваються складні фізичні та фізико-хімічні процеси, пов’язані з видаленням вільної, капілярно зв’язаної та адсорбційно утримуваної вологи, а також зі зміною стану органічних компонентів матеріалу. Обґрунтовано, що дослідження втрати маси залежно від температури та швидкості нагрівання дає змогу оцінити термічну стійкість насіння, виділити характерні температурні інтервали дегідратації та встановити енергетично різні форми зв’язку вологи. Особливу увагу приділено значенню цих характеристик для обґрунтування режимів сушіння, теплової підготовки і подальшої переробки насіння рицини. Отримані положення можуть бути використані під час розроблення технологій сушіння, математичного моделювання тепломасообміну та оцінки допустимих температурних меж обробки олійної сировини. /// EN: Castor seeds are a valuable technical oil raw material, the quality and technological suitability of which largely depend on the conditions of heat treatment before drying, pressing or extraction. During the heating process, not only moisture is removed from the material, but also the structural state of individual components changes, which can affect the oil yield, its quality, energy consumption of the process and the stability of seed storage. It has been established that the technological properties of seeds, as well as the efficiency of their processing, depend on humidity, density, porosity, geometric parameters and heating conditions. The paper investigates the thermal stability of castor seeds and the forms of moisture binding in their structure using thermal and thermogravimetric analysis methods. It is shown that during heating, castor seeds undergo complex physical and physicochemical transformations associated with the removal of free, capillary-bound and strongly bound moisture, as well as with the onset of thermal changes in the organic matrix. The use of TG and DTG curves makes it possible to determine the characteristic temperature ranges of dehydration, to estimate the rate of mass loss and to identify the transition from drying to undesirable thermal degradation. The study also confirms that the physical properties of castor seeds depend on moisture content, which affects heat and mass transfer during thermal treatment. The obtained results can be used to substantiate rational drying regimes, improve pre-treatment conditions before oil extraction and develop mathematical models of heat and mass transfer in castor seeds.
Research on thermostability and moisture bonding forms in castor seeds using thermal and thermogravimetric analysis methods
Keywords: насіння рицини; термостійкість; волога; форми зв’язку вологи; термічний аналіз; термо- гравіметричний аналіз; сушіння; теплова обробка; дегідратація; олійна сировина; castor seeds; heat resistance; moisture; forms of moisture bonding; thermal analysis; thermogravimetric analysis; drying; heat treatment; dehydration; oilseeds